O idoso na agenda de prioridades de pesquisa em saúde : um estudo no campo CTS - Anitelli, Lídia Bonfanti (2016)
This study aimed to investigate the knowledge and use of the National Agenda for Research Priorities in Health - elderly, the development of studies and research on gerontology and aging, from the theoretical contributions of the CTS and Gerontology, together with researchers from the Regional Health Departament III - Araraquara / SP. It is an exploratory and descriptive study carried out in six stages using plural methodological procedures: document analysis, collection of information by the CNPq Research Groups Directory and semi-structured interviews. Basing on te Resolution 466/12 all aspects of research with human beings were observed, was approved by CEP/UFSCAR number 1.062.001/2015. After gathering information, the data were analyzed pointing up as a result a strong presence of groups of studies on aging and gerontology registered in the CNPq Research Groups Directory (n=14) acting with the public universities of the study area where groups are concentrated. Leaders of groups (n = 11) have different academic backgrounds pointing trend toward interdisciplinarity. Despite the evidence shows strong tendency on studies and research in gerontology and aging, it was found that knowledge about the National Agenda for Research (Elderly) is limited from the human resources, requiring prioritize the dissemination of this information. The STS proves to be a privileged locus for such discussions both the interdisciplinary character with the Gerontology has been based, as the socio-historical dimensions and gaps identified in this study.